PREPRATION OF NEW NATIONAL MEDIA FOR CULTIVATION AND EFFECT OF SOME ENVIROMENTAL FACTORS ON GROWTH RATE OF OYSTER MUSHROOM - & et al., Chechan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was carried out to devise a local nutrient media for primary mycelium growth of two species of fungi belonging to the genus oyster mushroom Pleurotu snamed Pleurotus ostreatus and Pleurotus eryngii using tissue culture or mycelium inoculation for reproduction and production. Different natural material was used for this purpose involved Cumin, onion, oatmeal, banana peel, date seeds, garlic, alfalfa, flowers of palm pollenin a concentration ranged from 10 to 40 g/ L. The study was also focused on the effect of physical factors as temperatures and pH on growth rate of fungal mycelium. The results shown that the media prepared from cummins and onion powders have achieved best growth rate for the studied fungi Pleurotus ostreatus and Pleurotus eryngii which was 1.42 cm/ day in comparison with PDA where the growth rate was 0.71 cm/day. The best concentration of preparation of these medium was 20 g/L. The optimum pH could be adopted in the preparation of primary mycelium from two fungi was 6.5 which achieved the highest growth rate of 1.42 cm / day. While The optimum temperature for the development of this fungus was 25 C and a fungal growth rate 1.42cm/day.